A Case of Ataxia with Isolated Vitamin E Deficiency Initially Diagnosed as Friedreich's Ataxia. (16th February 2016) - Bonello, Michael; Ray, Partha
Abstract : Ataxia with isolated vitamin E deficiency (AVED) is a rare autosomal recessive condition that is caused by a mutation in the alpha tocopherol transfer protein gene. It is almost indistinguishable clinically from Friedreich's ataxia but with appropriate treatment its devastating neurological features can be prevented. Patients can present with a progressive cerebellar ataxia, pyramidal spasticity, and evidence of a neuropathy with absent deep tendon reflexes. It is important to screen for this condition on initial evaluation of a young patient presenting with progressive ataxia and it should be considered in patients with a long standing ataxia without any diagnosis in view of the potential therapeutics and genetic counselling. In this case report we present a patient who was initially diagnosed with Friedreich's ataxia but was later found to have AVED.